The Effect of Dividend Announcements on Change Stock Price After GMS to Date on Shares Jakarta Islamic Index (JII) Period 2017-2022 - Abdul Ghofur; Toto Sukarnoto; Dini Selasi; Gama Pratama (Ecobankers : Journal of Economy and Banking, 2026)
Changes. This study is motivated by the fact that investors who decide to invest in the Islamic capital market will certainly consider some information and analysis of an Islamic issuer. Dividend policy announcement is one of the information for investors to place their funds into an issuer. The purpose of this study was to determine the effect of dividend policy announcements on changes in stock prices after the AGM until the cum date on the Jakarta Islamic Index (JII) stocks for the period 2017-2022. This research uses a type of quantitative research with an event study method approach. The data collection method in this study uses secondary data documentation. This study took a sample of issuers that were consistently listed on the Jakarta Islamic Index (JII) for the period 2017-2022 and distributed dividends. In collecting data on dividend policy announcements (X), researchers took the nominal dividends distributed, while for changes in stock prices (Y) researchers took the closing price of shares with a range of AGM dates to cum date. Then the data that has been collected is processed to answer and find out the problems presented in this study. The data analysis method used in this research is panel data regression analysis and simple linear regression, which is processed using descriptive statistical analysis. Furthermore, where the results of the data processing are Announcement of cash dividend policy has a significant and negative effect on changes in stock prices of issuers of the Jakarta Islamic index (JII) for the period 2017-2022. This is evident from the results of the t test with a value of t count> t table, and a negative t value which indicates that the higher the dividend value, the lower the value of stock price changes. As well as the magnitude of the effect of the announcement of the cash dividend policy on changes in the share prices of issuers of the Jakarta Islamic index (JII) for the period 2017-2022 based on the results of the coefficient of determination test is 0.2669 or 26.69%. While the rest is influenced by other factors outside this study. Dividend policy announcements may not have a big effect on stock price changes due to other factors that affect stock price changes. This research, it is hoped that investors will further analyze the issuers to be selected not only from the dividend policy